Defective callose walls and cell plates during abnormal meiosis cause male-sterility in the oat mutant zbs1 - SHI Xiao, WU Jin-xia, ZHOU Hai-tao, YANG Xiao-hong, LI Tian-liang, ZHANG Xin-jun, YANG Cai, HAN Xiao (Biotechnology Research Institute, Chinese Academy of Agricultural Sciences/National Key Facility for Gene Resources and Gene Improvement, Beijing 100081, P.R.China Zhangjiakou Academy of Agricultural Sciences, Zhangjiakou 075000, P.R.China) (Journal of Integrative Agriculture, 2016)
During meiosis in flowering plants,degradation of the callose wall in tetrads releases newly produced microspores,which develop into mature pollen grains.In this study,we identified zbs1,a male-sterile mutant of naked oat（Avena nuda L.）that displayed complete spikelet sterility due to inviable mature pollen.The abnormal pollen grains originated from microspores with a defective callose wall and cell plate during meiosis.The defective callose wall and cell plate of the zbs1 mutant were detected by the labeling of cell wall epitopes（β-1,3-glucan） with immunogold during meiosis,and an abnormal chromosome configuration was observed by propidium iodide staining.The mature pollen grains of the zbs1 mutant were irregular in shape,and abnormal germination was observed by scanning electron microscopy.Together,our results indicate that the cause of male sterility in zbs1 is abnormal meiosis.